Ritual, Reform and Resistance in the Schoolified University. On the dangers of faith in education and the pleasures of pretending to taking it seriously - Sverker Lundin; Susanne Dodillet; Ditte Storck Christensen (Linköping University Electronic Press, 2018)
Why is there such a striking discrepancy between the flexibility, democracy and empowerment that the Bologna process aims for, and the superficial educational activities that it actually results in? Our answer is based on the ritual theory of the American anthropologist Roy Rappaport and the psychoanalytical framework of the Austrian philosopher Robert Pfaller. Interpreting schoolified education as a ritual, we argue that both the reform initiative and its ensuing educational activities should be interpreted as mainly productive of a certain appearance, of compliance with prominent norms of modern society: the norms are articulated in policy documents and enacted in educational activity. We take schoolified education to be a normal ritual, in that this appearance is accepted 'as if' it corresponded with reality, while at the same time most people are aware (in a certain sense) of its superficial and ritualistic character. A twist, however, is added by the fact that modern society is distinctly anti-ritualistic, and therefore constantly tries to make education work 'for real'. Drawing on Pfaller's distinction between belief and faith, we show that this pursuit of de-ritualisation actually makes education progressively more formalised and coercive.